1984
DOI: 10.1103/physrevlett.53.850
|View full text |Cite
|
Sign up to set email alerts
|

π-BondedN2on Fe(111): The Precursor for Dissociation

Abstract: N 2 chemisorbed on Fe(lll) is identified by photoelectron spectroscopy and highresolution electron energy-loss spectroscopy as a n-bonded surface complex in which both nitrogen atoms interact with the metal. This species forms the immediate precursor to dissociation.PACS numbers: 82.65.Jv, 31.20.Tz, 82.80.Di, 82.80.Pv Molecular nitrogen adsorption on transition metals has been studied in detail on various substrates by photoemission and vibrational spectroscopies, 1 and in all cases it has so far been concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(82 citation statements)
references
References 20 publications
7
74
0
1
Order By: Relevance
“…Fe(1 11) [30]. This peak is quite different from those for "end-on" physisorbed N 2 on metal surfaces, where two peaks at -406 and -401 eV were observed and attributed to the up and down N atoms, respectively [30].…”
Section: Xpsmentioning
confidence: 62%
See 2 more Smart Citations
“…Fe(1 11) [30]. This peak is quite different from those for "end-on" physisorbed N 2 on metal surfaces, where two peaks at -406 and -401 eV were observed and attributed to the up and down N atoms, respectively [30].…”
Section: Xpsmentioning
confidence: 62%
“…When N 2 adsorbed "end-on" on Ni(110) [31], W(100) [32] and Pt(111) [33], this mode was observed to be 265 meV or higher frequencies, while it was adsorbed "side-on" on Fe(1 11) [30], its vibrational frequency was shifted down to 185 meV. The observed 206 meV peak here, thus suggests a "side-on" adsorption of N 2 on Si(1 11).…”
Section: Hreerlsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) and (6), we used paramagnetic fcc Fe simulated within the magnetic SQS method and bcc crystals of V and Nb with theoretically calculated lattice parameters 3.03 and 3.30Å, respectively, which turned out to coincide with experimental ones (a V exp = 3.02Å [53] and a Nb exp = 3.30Å [53]). An isolated dimer with the experimental bond length 1.1Å was used as a reference state for N [54]. Because the van der Waals forces between graphite layers are not reproduced properly in the DFT-GGA calculations, for the reference state of C in Eq.…”
Section: B Impurity Solution Enthalpiesmentioning
confidence: 99%
“…Early investigations aimed to characterize the interaction of N 2 with Fe(111) identified two distinct molecular species on this face [7][8][9][10]: a weakly bound state with the molecular axis normal to the surface and a more strongly bound state with the molecule lying parallel to the surface. Using photoelectron spectroscopy and high-resolution electron energy loss spectroscopy, the latter was identified as the immediate precursor state to dissociation [7]. Molecular beam experiments directed to probe the dynamics of the N 2 /Fe(111) system showed that the N 2 translational kinetic energy can be efficiently used to promote reactivity on this surface [11].…”
Section: Introductionmentioning
confidence: 99%